REVIVAL OF THE SILK ROAD - Sevara Abdumalikovna Suleymanova (Galaxy International Interdisciplinary Research Journal, 2022)
The article deals with the history of the Great Silk Road, its significance in the social and trade and economic spheres, its role in the development of science in Central Asia. The role in development is analyzed. The influence of civilization on the relations of cooperation between peoples presents scientific conclusions about the importance of this historical path.